TECHNOLOGY INTEGRATION IN ENGLISH LANGUAGE TEACHING: ENHANCING LEARNING IN THE DIGITAL AGE (Ustozlar uchun, 2026)
This article explores the role of technology in English Language Teaching (ELT) and its impact on improving language learning outcomes. It examines how digital tools and online resources support communicative competence, learner autonomy, and motivation, particularly among A2–B1 level secondary school students. The study highlights practical strategies for integrating technology into English lessons while maintaining pedagogical balance and educational effectiveness.